Predicting sustained ventricular arrhythmias in dilated cardiomyopathy: a meta‐analysis and systematic review - Sammani, Arjan; Kayvanpour, Elham; Sedaghat-Hamedani, Farbod; Proctor, Tanja; Gi, Weng-Tein; Brözel, Alicia; Jensen, Katrin; Katus, Hugo; Meder, Benjamin (ESC heart failure, 2020)
Aims - Patients with non‐ischaemic dilated cardiomyopathy (DCM) are at increased risk of sudden cardiac death. Identification of patients that may benefit from implantable cardioverter‐defibrillator i...